Special-purpose geotechnical map on distribution of endo- and exogenous geological processes of the Republic of Guinea - A. S. Camara; V. V. Nevecheria; L. A. Yarg (Известия высших учебных заведений: Геология и разведка, 2024)
Background. Geodynamic processes pose a threat to the infrastructure of any country. Elucidation of these process is crucial for mitigating their impact on the economy, increasing the stability of structures, and ensuring the safety of the population.Aim. To compile a schematic map of the distribution of the main geological processes in the Republic of Guinea in order to identify the most favorable regions for development while minimizing the consequences of endo- and exogenous geological processes.Materials and methods. The research involved collection, analysis, and synthesis of geological, geographical, and stock materials. The authors’ own data was also used.Results. A special-purpose geotechnical map of geological processes in Guinea with a scale of M 1:7,500,000 was created. This map contains information on the spatial distribution of engineering-geological processes in the country. Seven processes that pose a risk to the infrastructure of the Republic of Guinea were identified and classified. The causes, conditions, and rates of process development are outlined.Conclusion. The developed special-purpose geotechnical map can be used when carrying out macroeconomic planning of the economic development of the country.